-19=-5x-4

Simple and best practice solution for -19=-5x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19=-5x-4 equation:


Simplifying
-19 = -5x + -4

Reorder the terms:
-19 = -4 + -5x

Solving
-19 = -4 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-19 + 5x = -4 + -5x + 5x

Combine like terms: -5x + 5x = 0
-19 + 5x = -4 + 0
-19 + 5x = -4

Add '19' to each side of the equation.
-19 + 19 + 5x = -4 + 19

Combine like terms: -19 + 19 = 0
0 + 5x = -4 + 19
5x = -4 + 19

Combine like terms: -4 + 19 = 15
5x = 15

Divide each side by '5'.
x = 3

Simplifying
x = 3

See similar equations:

| 4x-1/3 | | X+(x*.1)=11 | | logx+log(x-99)=2 | | 2(2x-5-4)=160-17 | | 40x=500 | | (40x)+(1.5(x))=500 | | 40x+1.5x=500 | | q^4+13q^2+36=0 | | 3(2a-3)=-(7-s) | | 8x+10=6x-9 | | 7500=2500m | | 76x+5=116 | | 4*x=32 | | 18y=2x | | 12x-10=360 | | 5w+6=-24 | | -7z=5-3(z+2) | | -x^3=216 | | (5-[(9-2)-3])/(-3-4-5)= | | (5-[(9-2)-3])/(-3-4-5) | | (6x-24)+(4x+12)=98 | | 0.5X+30=35 | | e^8t/-7e^t | | (5x-15)+2x=90 | | 3(4x-5)+2x+2=24 | | 100=110x | | 2x+3=7x-2 | | 10-(4n-2)=5-5n | | 14.50x+25x=1975 | | 1/(x^2-25)(x-7) | | 8+3x=18-12x | | -5(-7)(-6)= |

Equations solver categories